A Mouse Primary Hepatocyte Culture Model for Studies of Circadian Oscillation. Issue 4 (2nd December 2015) - Molyneux, Penny C.; Pyle, Lorna A.; Dillon, Martha; Harrington, Mary E.
Abstract: Circadian rhythms regulate many aspects of behavior and physiological processes, and, through external signals, help an organism entrain to its environment. These rhythms are driven by circadian clocks in many cells and tissues within our bodies, and are synchronized by a central pacemaker in the brain, the suprachiasmatic nucleus. Peripheral oscillators include the liver, whose circadian clock controls persistent daily rhythms in gene expression and in liver‐specific functions such as metabolic homeostasis and drug metabolism. Chronic circadian clock disruption, as in rotating shiftwork, has been linked to disorders including obesity, diabetes, and cardiovascular disease. The mouse primary hepatocyte culture model allows the examination of circadian rhythms in these cells. This article describes a transgenic mouse model that uses a bioluminescent reporter to examine the circadian properties of a core clock gene Period2 . Hepatocytes are isolated using a modified collagenase perfusion technique and cultured in a sandwich configuration, then sealed in a buffered medium containing luciferin for detection of whole‐culture or single‐cell bioluminescence. After synchronization by a medium change, cultures demonstrate coherent circadian period and phase measures of bioluminescence from the PERIOD2::LUCIFERASE reporter. © 2015 by John Wiley & Sons, Inc.